2017
DOI: 10.1038/celldisc.2017.21
|View full text |Cite
|
Sign up to set email alerts
|

miRNA-200c-3p is crucial in acute respiratory distress syndrome

Abstract: Influenza infection and pneumonia are known to cause much of their mortality by inducing acute respiratory distress syndrome (ARDS), which is the most severe form of acute lung injury (ALI). Angiotensin-converting enzyme 2 (ACE2), which is a negative regulator of angiotensin II in the renin–angiotensin system, has been reported to have a crucial role in ALI. Downregulation of ACE2 is always associated with the ALI or ARDS induced by avian influenza virus, severe acute respiratory syndrome-coronavirus, respirat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
118
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(123 citation statements)
references
References 74 publications
3
118
0
2
Order By: Relevance
“…41 Some studies showed that the inhibition of miR-200c relieved the acute lung injury induced by H5N1 virus infection in vivo. 42 In skin diseases, Magenta et al implicated miR-200c was up-regulated in psoriasis, which was related to the disease severity. 43 Hence, we further explore the im- family, which encodes a transcription factor with a highly conserved high-mobility group (HMG) DNA-binding domain.…”
Section: Discussionmentioning
confidence: 99%
“…41 Some studies showed that the inhibition of miR-200c relieved the acute lung injury induced by H5N1 virus infection in vivo. 42 In skin diseases, Magenta et al implicated miR-200c was up-regulated in psoriasis, which was related to the disease severity. 43 Hence, we further explore the im- family, which encodes a transcription factor with a highly conserved high-mobility group (HMG) DNA-binding domain.…”
Section: Discussionmentioning
confidence: 99%
“…MiR-34a levels are significantly higher in the lungs of neonatal rats exposed to hyperoxia compared with normal controls and miR-34a suppression improves the pulmonary phenotype and bronchopulmonary dysplasia-associated pulmonary arterial hypertension (14). Furthermore, plasma miR-200c-3p levels are much higher in patients with severe pneumonia compared with healthy controls (15).…”
Section: Introductionmentioning
confidence: 93%
“…Картина усложняется тем, что пневмонии могут развиваться вследствие вирусной или комбинированной инфекции. Было показано, что разные клеточные линии и даже разные типы легочного эпителия в ответ на инфекционные агенты экспрессируют разные наборы микроРНК [45,46]. Кроме типа клеток важно их микроокружение, так, на клеточной модели пневмонии после обработки ЛПС макрофагов изучали секрецию апоптотических телец и обнаружили в них изменение набора и количества микроРНК; при этом индуцировались miR-221 и miR-222.…”
Section: микрорнкunclassified
“…Подобная картина с повышением экспрессии miR-200c-3p наблюдалась при обработке культуры клеток ЛПС, синтетической двуцепочечной РНК (аналогом вирусной геномной РНК) и липотейхоевой кислотой (компонентом клеточной стенки грамположительных бактерий). Совокупность полученных результатов указывает на то, что супрессия АСЕ2 является универсальным механизмом при инфекции разными патогенами [46].…”
Section: вирусные пневмонииunclassified